Analisis Hubungan Antara Kadar Alkohol dengan Density dan pH Yang Terkandung di Dalam Red Wine Menggunakan Metode Regresi Linear Berganda - Muhammad Rafi Falih (Jurnal Riset Informatika dan Teknologi Informasi, 2025)
This study aims to analyze the relationship between alcohol content, density, and pH in red wine using multiple linear regression method. Alcohol content, density, and pH are important parameters that affect the quality and characteristics of red wine. In this study, red wine samples from different types and regional origins were analyzed to measure alcohol content, density, and pH using distillation, hydrometer, and pH meter techniques. The data obtained were then analyzed by multiple linear regression to identify the simultaneous influence of these variables on each other. The analysis showed that alcohol content had a significant effect on density, with a strong positive relationship. In addition, multiple linear regression revealed a significant effect between alcohol content and pH, although this effect was not linear and was influenced by other factors such as grape type and fermentation technique. The resulting regression model shows that alcohol content, density and pH are interrelated and provides a deeper understanding of the complex interactions between these parameters in red wine.